Perception of the quality of nursing care from the perspective of people hospitalized in a public hospital - Ruiz-Cerino, Juana María (Universidad de Sonora, 2020)
Introduction: From the moment a person enters a hospital until his discharge, nursing professionals constantly have a direct contact with the person; thus, evaluating how the patient perceived the quality of care he received allows the professionals to develop and implement strategies for continuous improvement. Objective: Identify the perception of the quality of nursing care from the perspective of people hospitalized in a public institution. Methodology: This was a cross-sectional descriptive study, using a sample comprised by 90 patients aged 18 and above who were identified through convenience sampling; the SERVQHOS-E instrument was applied with Cronbach´s Alpha of .87. Results: Regarding the quality of nursing care, an average of 1.97 points (SD = .626) of overall satisfaction was found. Most of patients indicated they were satisfied (67.8%) with the nursing care, followed by very satisfied (18.9%). Conclusions: More than half of the subjects who participated in this study, in a general manner perceived a good quality in the nursing care received.